Cetak Biru Sekolah Bertaraf Internasional - Hasanah, Muwahidah Nur (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2017)
Advanced school or an international school is a school that has had the confidence to grow and develop into a competitive school, not only at the local and national level, but also in the international arena. In this case the principal plays a major role in orienting the school innovation done so that schools can grow and develop in accordance with the ideals of the school that had been planned. One concrete manifestationof independent schools is able to deliver and facilitate the entire potential learners so that they can develop optimal fit with the talents, interests and abilities of learners.